Akibat Hukum Bagi Bank Terhadap Perjanjian Kredit Tanpa Persetujuan Dari Pasangan Debitur - Wishnu Kurniawan; Adilia Monica (Fakultas Hukum, Universitas Internasional Batam, 2015)
Under the Statistik Perbankan Indonesia Volume 13 No. 4, Period March 2015, published by the OJK showed that the number of banks and bank offices increased from year to year. Therefore, to increase the number of banks and bank offices can lead to increase competition of banking services and increase lending to the public. Nowadays, more and more types of banking products, primarily for credit products. In addition, one of the convenience provided that the credit agreement without the consent husband / wife debtor. The formulation of the problem in this research is a credit agreement without the consent of the husband/ wife of the debtor in accordance with statutory provisions and legal consequences for the banks as lenders to the credit agreement.This study is a normative legal research using secondary data with legal materials of primary legal materials, secondary, and tertiary as well as the method of data analysis is qualitative research and qualitative descriptive study.Based on this study, the result that associated with the credit agreement without the consent of the husband / wife debtor, then to the credit agreement will still have binding legal force. However, not all material collateral agreements still have binding legal force even without the consent of the husband / wife of the debtor, because the property needs to be seen in advance of what was pledged to the bank as collateral on the debt of the debtor material.